A Cross-Linguistic Study of BLOOD Metaphors in Afrikaans and Northern Sotho. Issue 1 (2nd January 2021) - Bosman, Nerina; Taljard, Elsabé
Abstract: Although a considerable body of corpus-based metaphor research—with Conceptual Metaphor Theory as theoretical framework and heuristic tool—has been published internationally, South African studies in this field are lagging behind. This article aims to demonstrate how cross-linguistic metaphor research within a cognitive semantics framework can benefit from lexical and corpus-linguistic methodologies, with specific reference to two lesser-resourced languages, namely, Afrikaans and Northern Sotho. Criticism against the so-called lexical approach that characterised the early work on conceptual metaphor has led to an increase in corpus-based investigation. Corpus-based research into metaphor has many advantages, but it depends on the availability of large, annotated corpora, which is not a resource that indigenous South African languages, including Afrikaans, can rely upon. Our article demonstrates how metaphor research can benefit from both methodologies. Relying also on another conceptual tool, metonymy, we identified three conceptual metaphors, namely LIFE IS BLOOD, EMOTIONS ARE BLOOD, and INHERITANCE IS BLOOD.